Human Resources Development In Yayasan Dana Sosial Al-Falah Surabaya On Islamic Economic Perspective - Harahap, Soritua Ahmad Ramdani (Li Falah: Journal of Islamic Economics and Business, 2018)
Humans are resource of power in economic development that acts as the caliph of Allah on earth that is demanded to be responsible for the continuity of development that bring maslahah people in the world and the hereafter. However, in reality the human resource problem itself is still very complex, such as the lack of optimal quality of human resources, evidenced by the high number of unemployed in Indonesia. Where open unemployment in February 2017 reached 5,33% from 5,50% in February 2016. This phenomenon is interesting to review from the standpoint of human resource development in an Islamic perspective. By using qualitative methods and data collection through observation, interview and documentation of the Al-Falah Social Fund Foundation (YDSF) Surabaya as a sample of research. Finally this article explains that human resource development at Al-Falah Social Fund Foundation (YDSF) Surabaya uses spiritual and material approach. Through these two approaches, human resource development goes with programs aimed at improving human resources both spiritually and the material. In addition, this article also explains the obstacles encountered along with the solution to be applied by the Al-Falah Social Fund Foundation (YDSF) in order to optimize the quality of human resources.